Utilization of Garcinia mangostana L. Peel as an Immunomodulator to Improve the Quality of Human Resources: A Systematic Review - Yunita Satya Pratiwi; Dina Mustika Rini; Ifwarisan Defri; Tawaffani Qubra; Nadien Mutia Intan Maulidi (Amerta Nutrition)
Background: Mangosteen (Garcinia mangostana L.) is recognized for its immunomodulatory properties, which can rejuvenate, regulate, and modulate immune system function. As a rich source of antioxidants, mangosteen peel has the potential to enhance immune responses and improve overall health status. However, further investigation into the biological mechanisms underlying its immunomodulatory effects remains limited.